Pembinaan Teknik Vokal Bagi Pemimpin Pujian di Calon Resort Kahayan Tengah Kabupaten Pulang Pisau - Sihombing, Octa Maria (Institut Agama Kristen Negeri Palangka Raya, 2024)
This research was motivated by the low understanding and knowledge of worship leaders on singing during worship. This research aims to provide guidance to worship leaders at Calon Resort GKE Kahayan Tengah, Pulang Pisau Regency as an effort to improve the ability of singing which was carried out during four months. The literature review used are breathing, posture, intonation, articulation, phrasering, and expression. This research was conducted in two cycles, each cycle consisting of planning, action, observation, and reflection with the results described in detail. The data collection techniques included tests, observations, interviews, and documentation. The results showed an increase in the singing ability of worship leaders at Calon Resort GKE Kahayan Tengah. The participants' average score from the pre-cycle to the first cycle was 69.2 and from the first cycle to the second cycle was 86.3 which increased well. Singing as a medium of communication with God, the worship leader has responsibility to help the congregation in building that communication. This research was expected to help the church and worship leaders in improving their singing skills and organizing a vocal coaching periodically so that the singing ability of worship leaders will increase.